Controlled coalescence of two immiscible droplets for Janus emulsions in a microfluidic device1. Issue 41 (7th May 2015) - Zhang, Ming-Yu; Zhao, Hong; Xu, Jian-Hong; Luo, Guang-Sheng
<x xml:space="preserve">Abstract</x> We developed a simple microfluidic device to prepare Janus emulsions by the controlled coalescence of two immiscible droplets.